Changes in the Marriage Agreement in Mixed Marriages in a Positive Indonesian Legal Perspective - Moh. Asep Suharna (IHSA Institute, 2022)
Many cases may occur in some areas, where changes to the marriage agreement are made after the marriage takes place and the deed of amendment to the marriage agreement has been made by a notary. In view of Article 147 of the Civil Code which states that the Marriage Agreement is threatened with cancellation if it is not made by a Notary. The marriage agreement between the two prospective husband and wife is made, either in writing or in deed, either under the hand or in an authentic form made by an authorized public official. However, to provide maximum and binding protection for the parties concerned, the marriage agreement should be made in the form of an authentic deed. The purpose of this paper is to analyze the notary's responsibility for changes to the marriage agreement after the marriage and the legal consequences of changing the marriage agreement in mixed marriages for the husband and wife concerned and for third parties. The research method used in this research is descriptive analytical, with a normative juridical approach. This research was conducted by means of library research and field research with data collection techniques through documentation studies and interviews as well as data analysis methods used in this study using qualitative juridical analysis. Based on the results of research and discussion, the following conclusions can be drawn: First, if the notary commits an unlawful act in the amendment of the marriage agreement which causes harm to a third party, the notary must be held accountable for his actions by being subject to civil sanctions in the form of reimbursement of costs or compensation to the party who violated the law. harmed; Second, the legal consequences of changing the marriage agreement which have been ratified by the Marriage/Marriage Registrar and made in a Notary deed, will bind and apply as law for the parties and third parties with an interest in the amendment to the marriage agreement.